IMPROVING THE METHODOLOGY OF USING PEDAGOGICAL SOFTWARE TOOLS FOR STUDENTS’ INDEPENDENT SELF-DEVELOPMENT IN AN INFORMATION-EDUCATIONAL ENVIRONMENT (Multidisciplinary Journal of Science and Technology, 2026)
This study investigates methodological approaches to improving the use of pedagogical software tools in fostering students’ independent self-development within an information-educational environment. A quasi-experimental design involving control and experimental groups was implemented. The findings demonstrate statistically significant growth in self-regulated learning, digital competence, and academic performance indicators.